Urgensi Pengaturan dan Perlindungan Hukum Bagi Pekerja Rumah Tangga di Indonesia - Anugrah, Cahyo Putra Fatkhuriza; Ruslie, Ahmad Sholikhin (Media Hukum Indonesia (MHI), 2024)
Domestic Workers (PRT) in Indonesia have a major contribution in supporting the sustainability of the economy and social life of the community. However, their existence is often ignored in legal regulations that should provide proper protection and recognition. The absence of specific laws governing the rights and obligations of domestic workers creates significant legal loopholes, so that many domestic workers face the risk of exploitation, discrimination, and even violence. This study aims to examine the urgency of legal regulations for domestic workers, with a focus on analyzing the weaknesses of current regulations and recommendations for the formation of more inclusive and fair policies. So that in this study there is a formulation of problem one, namely How is the legal regulation on Domestic Workers, and the formulation of problem two How is the legal protection for Domestic Workers. So to what extent are existing legal regulations able to protect domestic workers and what steps need to be taken to improve this protection. This study uses a normative legal method, with a legislative and conceptual approach. The data used includes primary legal materials, such as applicable laws, and secondary legal materials in the form of related literature, which are analyzed qualitatively to gain an in-depth understanding. The results of the study show that legal protection for domestic workers is very minimal. Domestic workers are not recognized as formal workers, so they do not receive basic rights such as minimum wages, decent working hours, and access to social security.